Generation of mammalian cell lines with gene knock-down for human MCHR2 - Yuan, C.; Lu, W.; Xiang, T.; Yi, F.; Liu, G.; Ren, G.; Song, F. (Cellular and Molecular Biology, 2010)
Appetite regulating neuropeptide melanin-concentrating hormone (MCH) has been implicated in obesity. It functions through its two receptors MCHR1 and MCHR2. While MCH and MCHR1 have been studied more extensively, the function of MCHR2 remains largely unknown, due to the lack of suitable in vitro and in vivo models. To create an in vitro system of genetic knock-down of MCHR2 in mammalian cells, we constructed four small hairpin RNAs (shRNAs) against human MCHR2 in eukaryotic expression vector, and transfected the plasmids into CHO cells that stably express human MCHR2. Using the empty vector or a negative shRNA control plasmid, we show that MCHR2-shRNAs suppressed 45.8% - 66.4% of MCHR2 expression at both mRNA and protein levels. As the result, in cells carrying the MCHR2-shRNAs, binding of MCHR2 to MCH was decreased by 39.4% - 78.7% accompanied by a similar decrease in affinity of the receptor to ligand by 40.9% - 81.9%. These cells still respond to MCH treatment, but intracellular Ca2+ release as the downstream signaling event was also decreased by 114.8% - 822.4%. Together, this study generated a set of shRNAs and cell lines as valuable reagents for further study on MCHR2 functions. These results will ultimately help to advance our knowledge about appetite regulating neuropeptide receptors.